Six Thinking Hats and Think - Pair - Share Collaborative Learning Technique for Enhancing Physics Learning Achievement for Secondary School Level 4 - Ngansom, Wipada; Nasaree, Weerachai; Mahapattanathai, Prapat (Journal of Advanced Development in Engineering and Science, 2023)
This experimental research was to study the old Think-Pair-Share collaborative learning technique together with the Six Thinking Hats by applying a new collaborative learning technique as the Six Thinking Hats and Think-Pair-Share that it is a model for physics learning achievement for 36 students in secondary school level 4, science ? mathematics study program at the Demonstration School of Ramkhamhaeng University. A model of learning documents using for the comparison of learning achievements between the old Think-Pair-Share technique and the Six Thinking Hats and Think-PairShare technique for 36 students (6 groups) was developed.The developed learning documents with the efficiency of 1.58 according to Meguigans? formula were applied for the two groups of students by using the Pretest Posttest Control Group Design. The results showed that the learning achievement of the Six Thinking Hats and Think-Pair-Share group was higher than the normal Think-Pair-Share group.